Existence and uniqueness of the competitive equilibrium for infinite dimensional economies - Accinelli, Elvio (Estudios de Economía, 2016)
In this paper we prove the existence of an equilibrium theorem and we obtain a condition for uniqueness of equilibrium in infinite dimensional economics using the excess utility function.